Mandatory Audit Firm Rotation And Big4 Effect On Audit Quality: Evidence From South Korea - Jong , seo Choi; Hyoung , joo Lim; Mal, Dafydd (Asian Academy of Management (AAM), 2017)
In South Korea, due to concurrent fnancial scandals, Korean legislators implemented two major audit policies in the 2000s; the mandatory audit “partner” rotation policy in 2000 and the mandatory audit “frm” rotation policy in 2006. The mandatory audit “frm” rotation policy was introduced as a mean to improve audit quality based on the auditor entrenchment hypothesis. In this paper, we compare the audit quality of frms subjected to mandatory audit “frm” rotation with two benchmark groups, a sample that adopted the policy voluntarily; the second group consists of the mandatory “frm” rotation sample in years prior, a period frms were subject to mandatory audit “partner” rotation. Using accrual-based measures as proxies for audit quality, we fnd evidence that audit quality of the mandatory rotation frm sample is lower compared to frms that voluntarily adopted the policy. Furthermore, we fnd evidence that audit quality of the mandatory rotation frm sample is lower compared to the mandatory audit partner frm sample. Additionally, we also fnd evidence that the mandatory audit frms rotation sample whose auditors were rotated from Non-Big4 to Big4 are generally associated with lower levels of abnormal accruals consistent with the argument that the audit quality of Big4 accounting frms is superior to Non-Big4 frms. Finally, longer audit tenure and switches to Big4 audit frms generally have a positive effect upon audit quality. These fndings suggest that extended audit tenure improves audit quality due to accounting frm’s